Prevalence of echogenic intracardiac focus and its association with fetal aneuploidy and adverse perinatal outcomes in Turkish pregnancies - Sancakli Usta, Ceyda; Bahar Bulbul, Cagla (Annals of Medical Research, 2021)
Aim: The association between echogenic intracardiac focus (EIF) and fetal aneuploidy is well established, with a recognized ethnic variation. This study aimed to investigate the prevalence of EIF in Turkish pregnancies and examine its association with fetal aneuploidy and adverse pregnancy outcomes.Material and Methods: We conducted a retrospective cohort study of second-trimester obstetric ultrasonography (16–24 weeks) at a university hospital for over 4 years. During the evaluation, all pregnancies with and without EIF were divided into three groups; Group 1: control group (randomly selected patients without EIF, n = 100); Group 2: isolated EIF group, (EIF is the sole finding, n = 45) and Group 3: non-isolated EIF group, (EIF with accompanying other ultrasound findings for fetal aneuploidy and/or presence of congenital anomalies, n = 21). The pregnancy outcomes of patients with isolated and non-isolated EIF and control group were compared.Results: Overall, 2590 obstetric sonograms were examined, with an EIF prevalence of 2.55%. The presence of other ultrasonography findings and/or congenital anomalies accompanying EIF was associated with an increased risk of fetal aneuploidy, and 2 of 21 (9.5%) pregnancies in the non-isolated EIF group had fetal aneuploidy. In addition, non-isolated EIF was associated with perinatal mortality, preterm delivery, and polyhydramnios when compared to controls and isolated EIF pregnancies. There was no difference in the pregnancy outcomes between control and patients with isolated EIF.Conclusion: EIF is a rare occurrence in Turkish pregnancies and as a sole finding, it is not associated with fetal aneuploidy or other adverse pregnancy outcomes. However, the presence of ultrasonography findings and/or congenital anomalies accompanying EIF was associated with an increased rate of fetal aneuploidy and adverse pregnancy outcomes.